1997
DOI: 10.1177/106002809703101110
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine: A New Antipsychotic Agent with Efficacy in the Management of Schizophrenia

Abstract: The exact place of olanzapine in the therapy of psychotic patients remains unclear, as more data are needed to evaluate the long-term efficacy of this agent, its impact on negative symptoms, and its potential use in patients resistant to the standard agents. Despite limitations in the current database, olanzapine is a promising treatment option for patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Despite the methodological shortcomings and flaws of retrospective chart analysis, these results are consistent with the findings of several multicentre, randomized, controlled, double-blind studies in indicating that olanzapine is a safe and effective antipsychotic medication (4)(5)(6)(7)11). The present chart review adds evidence that it is well suited for use in a population of elderly individuals with dementia and psychotic complications.…”
Section: Limitationssupporting
confidence: 83%
See 2 more Smart Citations
“…Despite the methodological shortcomings and flaws of retrospective chart analysis, these results are consistent with the findings of several multicentre, randomized, controlled, double-blind studies in indicating that olanzapine is a safe and effective antipsychotic medication (4)(5)(6)(7)11). The present chart review adds evidence that it is well suited for use in a population of elderly individuals with dementia and psychotic complications.…”
Section: Limitationssupporting
confidence: 83%
“…In comparison studies, they have shown superior efficacy in the treatment of certain behavioural symptoms, such as decreased verbal fluency and apathy, and in the treatment of patients refractory to typical antipsychotics (1,2). At the same time, they have been shown to reduce the positive symptoms of psychosis, including those caused by dementia (3), at least as well as conventional neuroleptics (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In another review, 205 more improvement and less attrition was also found in those treated with olanzapine than in those treated with typical comparators. In a third review, 206 olanzapine was found to be equivalent in effectiveness to typical antipsychotic drugs and produced fewer movement disorders. None of these findings differed substantially from the findings of the Cochrane review.…”
Section: Other Systematic Reviewsmentioning
confidence: 99%
“…Adolescents experience considerable intra-individual variability across time despite stable dosing, which appears somewhat greater in adolescents than adults 85,89. The concentration-to-dose ratio of olanzapine appears generally linear 78. However, adolescents appear to have a higher (~34%) concentration-to-dose ratio than adults even after adjustment for weight 90…”
Section: Olanzapine Pharmacology and Pharmacokineticsmentioning
confidence: 99%